A Low-profile Wide Band "S" Shaped Rectangular Dielectric Resonator Antenna for "X" Band Application. Issue 4 (4th July 2021) - Vinodha, E.; Raghavan, S.
Abstract : The main goal of this article is to design a low-profile wide band Rectangular Dielectric Resonator Antenna (RDRA). The proposed "S" shaped rectangular DRA is excited by means of a popular microstrip line feeding. By using "S" shaped design, our proposed DRA yields an impedance bandwidth of 32% from 9.2 to 12.48 GHz, covering "X" band frequency. The proposed antenna has a wide impedance bandwidth, extremely low profile with the volume of 447 mm 3, and a thickness equal to 2.5 mm. This design provides stable radiation patterns and high radiation efficiency. The proposed design is compared with some other designs in the literature in order to emphasize its significance. The proposed RDRA was fabricated and its characteristics were tested. Excellent agreement between simulated and measured ones was obtained.